Hubungan Pemeriksaan Kehamilan dengan Risiko Kehamilan Menggunakan Skoring Poeji Rochyati pada Ibu Hamil Trimester III - Dyah Tri Apriliasari; Nurul Pujiastuti (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Pregnancy is one of the physiological processes that may be expected by most women, this pregnancy can be a physiological state or also a pathological state. To find out the risks in pregnancy, it is necessary to do a pregnancy check-up which is usually done by the mother in the first week until the last week before delivery, this examination is to find out the risk of pregnancy that may be suffered by the mother during the pregnancy by using poejirochyati scoring, by looking at the mother's compliance in performing pregnancy test. The purpose of this study was to determine the relationship of antenatal care with the risk of pregnancy using Poeji rochyati scoring in trimester 3 pregnant women at the Ardimuyo Singosari Public Health Center Malang on 22 October - 22 November 2020. The research design used was analytic correlation using a cross sectional approach. The sampling technique used was purposive sampling, the number of samples taken was 42 samples. The results of this study indicate a relationship between antenatal care with the risk of pregnancy using a score of rochyati poeji. After doing the chi square test, P value = 0.003 <α = 0.05 thus H1 is accepted and H0 is rejected so that it can be concluded that there is a relationship between pregnancy examination and the risk of pregnancy using poeji rochyati scoring in third trimester pregnant women. Scoring Poeji rochyati can be used by health workers to see the risk of pregnancy in pregnant women.